2016
DOI: 10.3389/fnagi.2016.00211
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Blood Flow Alterations as Assessed by 3D ASL in Cognitive Impairment in Patients with Subcortical Vascular Cognitive Impairment: A Marker for Disease Severity

Abstract: Abnormal reductions in cortical cerebral blood flow (CBF) have been identified in subcortical vascular cognitive impairment (SVCI). However, little is known about the pattern of CBF reduction in relation with the degree of cognitive impairment. CBF measured with three-dimensional (3D) Arterial Spin Labeling (ASL) perfusion magnetic resonance imaging (MRI) helps detect functional changes in subjects with SVCI. We aimed to compare CBF maps in subcortical ischemic vascular disease (SIVD) subjects with and without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 56 publications
1
41
0
Order By: Relevance
“…In accordance with the criteria suggested by Galluzzi et al (2005), SIVD was defined as subcortical white matter hyperintensities (WMHs) that are visible on T2-weighted imaging with at least one lacunar infarct. The exclusion criteria ( Table 1 ) were applied as previously described (Sun et al, 2011, 2016). Patients were excluded if they presented with calcification or microbleeds in deep gray matter nuclei, including the bilateral pulvinar nucleus of the thalamus, head of caudate nucleus, globus pallidus, putamen, hippocampus, substantia nigra, and red nucleus with dark spots and negative susceptibility.…”
Section: Methodsmentioning
confidence: 99%
“…In accordance with the criteria suggested by Galluzzi et al (2005), SIVD was defined as subcortical white matter hyperintensities (WMHs) that are visible on T2-weighted imaging with at least one lacunar infarct. The exclusion criteria ( Table 1 ) were applied as previously described (Sun et al, 2011, 2016). Patients were excluded if they presented with calcification or microbleeds in deep gray matter nuclei, including the bilateral pulvinar nucleus of the thalamus, head of caudate nucleus, globus pallidus, putamen, hippocampus, substantia nigra, and red nucleus with dark spots and negative susceptibility.…”
Section: Methodsmentioning
confidence: 99%
“… 71 Another study explored the relationship between CBF and cognition in patients with SVCI and showed that the reduced CBF in the frontal lobe, temporal lobe and several deep nuclei was associated with the degree of cognitive impairment in patients with SVCI. 73 Notably, the CBF fluctuations of different brain areas may be concurrent, contributing to the concept of CBF connectivity based on CBF fluctuations. 74 The functional networks identified using CBF connectivity display similar spatial patterns with networks based on BOLD signals, including DMN and executive control network.…”
Section: Considerations For Multimodality Fusion In Svcimentioning
confidence: 99%
“…Endothelial function is closely linked to the control of cerebrovascular reactivity, which is essential for creating a favourable environment for neurons, by maintaining energy-dependent processes and removing metabolic waste [ 54 – 56 ]. It has been suggested that impaired cerebrovascular reactivity is not only related to CVDs, but can also be associated with dementia [ 57 ]. Studies have explored the association between physiological (i.e.…”
Section: Endothelial Dysfunction No and Cognitive Impairmentmentioning
confidence: 99%